No Risk, No Differences. Neural Correlates of Temperamental Traits Revealed Using Naturalistic fMRI Method - Bierzynska, Maria; Sobczak, Pamela Anna; Kozak, Anna; Bielecki, Maksymilian; Strelau, Jan; Kossut, Malgorzata Maria (Frontiers in Psychology, 2019)
The main goal of this study was to identify the moderating role of temperamental traits, as defined by Strelau’s Regulative Theory of Temperament, in explaining brain activity evoked by video stimuli of varying stimulatory value. fMRI scans were performed in a group of 61 young females in the luteal phase of the menstrual cycle. The validity of stimulus selection had been verified prior to the main study by collecting declarative measures of affective reactions, including valence, arousal, and basic emotions ratings. The choice of dynamic and complex video-stimuli allowed us to induce high levels of arousal effectively. Three categories of movies used in the experiment included neutral, low arousing, and highly arousing scenes. Movies classified into the last category depicted extreme-sport activities allowing us to confront the subjects with recordings potentially life-threatening situations. Results of the study revealed that activation of orbitofrontal cortex in highly arousing conditions is linked to the levels of activity, while traits of perseverance and emotional reactivity were negatively correlated with the BOLD signal in this structure. Low arousing movies evoked higher activation of the amygdala and left hippocampus in emotionally reactive subjects. Obtained results might be coherently interpreted in the light of RTT theory, therefore providing its first validation using functional brain imaging.